Tax Planning, Audit Quality, Audit Opinion, Leverage, and Profitability as a Determinant of Timeless Reporting - Titik Dwiyani; Margaretha Prihatiningsih; Darmanto Darmanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of the research entitled ‘Tax Planning, Audit Quality, Audit Opinion, Leverage, and Profitability on Timeless Reporting’ is to find out the effect of Tax Planning, Audit Quality, Audit Opinion, Leverage, and ROA variable on Timeless Reporting. The population and sample used in this research is manufacture company registered in BEI in 2016 – 2018. This sample was 123 manufactures which was chosen by using stratified purposive sampling method. The research data analysis used double linier regression analysis and used SPSS. The result of partial analysis test showed that tax planning and audit quality did not affect toward timeliness reporting, but the audit opinion and leverage which were measured by debt to asset ratio (DAR), and profitability which was measured by return to asset (ROA) were proved affected on timeliness reporting. Simultaneous test result showed dependent variable simultaneously affected on tax avoidance. Keyword: Tax Planning, Audit Quality, Audit Opinion, Leverege, ROA, Timeliness Reporting